Nomogram Based on Lactate Dehydrogenase-to-Albumin Ratio (LAR) and Platelet-to-Lymphocyte Ratio (PLR) for Predicting Survival in Nasopharyngeal Carcinoma - Peng RR; Liang ZG; Chen KH; Li L; Qu S; Zhu XD (Dove Medical Press, 2021)
Ru-Rong Peng,1 Zhong-Guo Liang,1 Kai-Hua Chen,1 Ling Li,1 Song Qu,1 Xiao-Dong Zhu1,2 1Department of Radiation Oncology, Guangxi Medical University Cancer Hospital, Nanning, People’s Republic of China; 2Department of Oncology, Affiliated Wu-Ming Hospital of Guangxi Medical University, Nanning, People’s Republic of ChinaCorrespondence: Xiao-Dong ZhuDepartment of Radiation Oncology, Guangxi Medical University Cancer Hospital, 71 He-di Road, Nanning, 530021, People’s Republic of ChinaTel +86 15778028340Email zhuxdonggxmu@126.comPurpose: The prognosis of inflammation-related indicators like lactate dehydrogenase/albumin ratio (LAR) and the platelet/lymphocyte ratio (PLR) in nasopharyngeal carcinoma (NPC) is not yet clear. Our objective is to establish and verify the nomogram using LAR and PLR ratio for the first time to explore the prognostic value in NPC.Patients and Methods: This was a retrospective collection of 1661 patients with non-metastatic NPC admitted to our hospital from 2010 to 2017. The final variables of overall survival (OS) and progression-free survival (PFS) were selected by Cox regression analysis to establish nomograms, and the methods to verify the prediction precision and discriminative ability of the nomograms were concordance index (C index), the receiver operating characteristic (ROC) curve and calibration curve. The risk stratification was carried out through the nomograms and compared with the current staging system by the Kaplan–Meier methods.Results: Multivariate Cox analysis resulted that age, plasma Epstein–Barr Virus (EBV) DNA, T stage, N stage, white blood cells (WBC), PLR and LAR were independent prognostic risk factors for OS and PFS, and sex is an independent prognostic risk factor for OS. The C-indexes of OS nomogram were 0.722 (95% CI: 0.706– 0.738) and 0.747 (95% CI: 0.717– 0.777) in the training cohort and validation cohort, which were statistically higher than the current 8th AJCC staging system (0.646 and 0.688). The C-indexes of PFS nomogram were 0.696 (95% CI: 0.680– 0.713) and 0.690 (95% CI: 0.660– 0.720), which were also statistically higher than the current 8th AJCC staging system (0.632 and 0.666). Otherwise, ROC curves and the calibration curve for probability also confirmed satisfied consistency with actual observations.Conclusion: LAR is a novel useful independent factor in NPC. The proposed nomogram LAR and PLR resulted in more accurate prognostic prediction than current staging system for NPC patients.Keywords: intensity-modulated radiotherapy, nasopharyngeal carcinoma, lactate dehydrogenase to albumin ratio, platelet-to-lymphocyte ratio, tumor–node–metastasis staging system